Implementasi Pentingnya Persatuan Melalui Toleransi dan Kerjasama Generasi Muda Bangsa Era Globalisasi - Marchell S P Siburian; Edy Soesanto; Rayhan Zain Alfataa (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
Indonesia, as an archipelagic country rich in ethnic, cultural and religious diversity, faces great challenges in maintaining unity amidst differences. In this context, tolerance and cooperation between communities are important foundations for strengthening national unity. Tolerance is not only about respecting differences, but also about understanding and accepting diversity as a force that can enrich social life. Meanwhile, cooperation creates synergy between individuals and groups to achieve common goals, making diversity a tool for building harmony. National unity is a solid foundation for the younger generation to achieve a bright future. In an era of globalization full of dynamics, unity becomes increasingly crucial. Without unity, various challenges such as division, radicalism and instability will threaten the survival of the nation. The young generation as agents of change has a central role in maintaining and strengthening unity. By uniting, the young generation can create strong synergy to overcome various problems and advance the nation.